Short- and long-term survival after ST-elevation myocardial infarction treated with pharmacoinvasive versus primary percutaneous coronary intervention strategy: a prospective cohort study - Sigrun Halvorsen; Jon Michael Gran; Kristin Kvakkestad (BMJ Open)
Objective Compare survival in patients with ST-elevation myocardial infarction (STEMI) treated with a pharmacoinvasive (PI) or primary percutaneous coronary intervention (pPCI) strategy based on estimated time to PCI.Design Prospective observational cohort study. Consecutive STEMI patients were registered on admission to our PCI centre and classified in a PI or pPCI group, based on the reperfusion strategy chosen in the prehospital or local hospital location. Time and cause of death was provided by the Norwegian Cause of Death registry. Mortality at 30 days, Kaplan-Meier survival and incidence of cardiovascular (CV) death was estimated. Adjusted effect of PI versus pPCI strategy on survival was estimated using logistic and Cox regression and propensity score weighting.Setting Single-centre registry in Norway during 2005–2011, within a regional STEMI network allocating patients to a PI strategy if estimated time to PCI >120 min.Primary outcomes 30-day mortality and survival during follow-up.Secondary outcome Incidence of CV death during follow-up.Results 4061 STEMI patients <80 years were included, 527 (13%) treated with a PI strategy and 3534 (87%) with a pPCI strategy. Median symptom-to-needle time was 110 min (25–75th percentile 75–163) in the PI group vs symptom-to-balloon 230 min (149–435) in the pPCI group. 30-day mortality was 3.2% and 5.0% in the PI and pPCI groups (ORadjusted0.58 (95% CI 0.30 to 1.13)) and 8-year survival was 85.9% (95% CI 80.9% to 89.6%) and 79.3% (95% CI 76.9% to 81.6%), respectively (HRadjusted 0.72 (95% CI 0.53 to 0.99)). Unadjusted incidence of 8-year CV death was 7.0% (95% CI 4.4% to 10.4%) in the PI group vs 12.4% (95% CI 9.9% to 15.2%) in the pPCI group. Adjusted long-term CV death was also lower in the PI group.Conclusion STEMI patients treated with a PI strategy experienced better survival compared with a pPCI strategy, also when adjusting for baseline characteristics. This supports using a PI strategy for eligible STEMI patients when pPCI cannot be performed within 120 min.